C-Reactive Protein (CRP) Levels in Early Diagnosis of Neonatal Sepsis - Tariq Saeed, Muhammad Zahoor Ul Haq, Fazal-E-Rabi Subhani, Rubina Zulfiqar, Tariq Mahmood Raja, (Journal of Rawalpindi Medical College, 2014)
Background: To determine the validity of CRP in the early diagnosis of neonatal sepsis, keeping blood culture as gold standard. Patients and Methods: In this cross sectional study 373 full term neonates of either gender, suspected of having sepsis were included. Blood samples of these patients were collected for C-reactive protein and blood culture. The results of CRP were validated by blood culture findings. Results: CRP was found to be positive in 101 cases. Blood culture was positive in 226 cases. The main organisms isolated were Acinetobacter, Klebsiella pneumoniae, Staphylococcus aureus, Escherichia coli, Pseudomonas and Proteus. The sensitivity and specificity of CRP were 45.0% and 65.1% respectively while the Positive Predictive Value and Negative Predictive Value were 66.0% and 44.1%, respectively. Conclusion: C-reactive protein is an inexpensive and simple test to perform. Sensitivity of C- reactive was detected to be low.